(untitled) (Journal of Hama University, 2022)
This clinical trial aimed to compare the potential effect of platelet rich plasma (PRP) and injectable platelet rich fibrin(I-PRF) on gingival invagination formation 60 patients who required fixed orthodontic treatment and maxillary first premolar extractions participated in this trial , they were divided into three different groups: The control group: 20 patients (12 females, 8 males; mean age, 20.6±2.1 years) didn’t receive any injections The PRP group: 20 patients ( 10 females, 10 males; mean age, 20.9±2.3 years) received PRP injections The I-PRF group: 20 patients (14 females, 6 male; mean age, 21.8±1.8 years) received I-prf injections PRP and I-PRF injections were done around the upper canines. 0,8 weeks after the start of the retraction. incidence ( Presence/absence ) and severity of gingival invaginations were recorded in each group Gingival invaginations developed more frequently in the control group ( 80%) than the PRP group (55% ) and I-PRF group (45%).severity of gingival invaginations was lower in the experimental groups with a statistically significant difference. Gingival invaginations development is a frequent finding during orthodontic space closure and Local injection of PRP and I-PRF in the present study resulted in reducing its incidence and severity